Precision Medicine in Graves’ Disease: CD40 Gene Variants Predict Clinical Response to an Anti-CD40 Monoclonal Antibody - Faustino, Larissa C.; Kahaly, George J.; Frommer, Lara; Concepcion, Erlinda; Stefan-Lifshitz, Mihaela; Tomer, Yaron (Frontiers in Endocrinology, 2021)
Background: CD40, a key co-stimulatory molecule expressed on antigen presenting cells, is genetically associated with a number of autoimmune diseases including Graves’ disease (GD). Therefore, recently therapies targeting CD40 have been developed including the anti-CD40 monoclonal antibody Iscalimab. In a recent pilot study Iscalimab was shown to induce clinical remission in 50% of GD patients, but the reason why only 50% of GD patients responded is not known. The aim of our study was to test the hypothesis that specific CD40 SNP genotypes and haplotypes are associated with clinical response of GD patients to Iscalimab. Methods: We extracted genomic DNA from the whole blood of 13 GD patients treated with Iscalimab, and genotyped seven CD40 single nucleotide polymorphisms (SNPs) associated with autoimmunity. Additionally, we analyzed CD40 mRNA expression levels in whole blood. The patients’ CD40 SNP genotypes and mRNA levels were tested for association with clinical response to Iscalimab. Results: Three common haplotypes, designated haplotypes A, B, and C, were identified. Haplotypes B and C were associated with higher CD40 mRNA levels and clinical response to Iscalimab, while haplotype A was associated with decreased CD40 mRNA levels and no response to Iscalimab. Conclusion: Our data suggest that genetic polymorphisms in the CD40 gene drive its expression levels and response to Iscalimab. Polymorphisms associated with higher CD40 levels are also associated with clinical response to CD40-targeted therapies. These results set the stage to implementing precision medicine in the therapeutic approach to GD.